Hydroxyapatite deposition study through polymeric process on commercially pure Ti surfaces modified by laser beam irradiation - Ribeiro, Alexandre Antunes; Costa Marques, Rodrigo Fernando [UNESP]; Guastaldi, Antonio Carlos [UNESP]; de Carvalho Campos, Joao Sinezio (Springer, 2009)
Many techniques have been used to coat metallic substrate with bioceramics. The aim of this study was to study the physical-chemical characteristics of polyvinylidene fluoride (alpha-PVDF)/hydroxyapatite (HA) composite coating, obtained by casting method, on commercially pure titanium (alpha-CP Ti) substrate surface modified by laser beam irradiation. The preparation of coating was done for mixing alpha-PVDF pellets shape dissolved in dimethylacetamide (DMA) with HA/DMA emulsion. The mixture was poured onto the alpha-CP Ti sample and left to dry in an oven. CP Ti plates were coated with alpha-PVDF/HA composite film, in proportions of 100/00 and 60/40 in weight, and characterized by particle size analysis, scanning electron microscopy, energy dispersive spectroscopy (EDS), X-ray diffractometry, thickness measurement and contact angle. Uniform coating with a small thickness variation along the coated surface was successfully obtained.